Wcielenie Chrystusa w świetle "Liber apotheosis" i "Liber cathemerinon" Aureliusza Prudencjusza Klemensa - Pyzik-Turska, Małgorzata (Vox Patrum, 2013)
The following article covers the issues regarding the Incarnation of Jesus Christ presented in a poetic manner in Liber Apotheosis and Liber Cathemerinon by Aurelius Prudentius Clemens. The first part illustrates the references to the fact of Birth taken from the Old Testament. It focuses primarily on the messianic prophecies – the prophecies of the Messiah, who was to be sent to the world. The second part presents the circumstances and the place of the Bethlehem event. The poetic depictions of the place and time of the Nativity as well as the consequences arising from accepting Christ as the Saviour sent by God have been presented in reference to the evangelical accounts. The third part discusses the results of the Incarnation that were illustrated in a poetical form by Aurelius Prudentius Clemens. Thus, the article presents the fact of the exaltation of human body resulting from the absolution of sins, redemption of man, as well as the emphasis of human dignity.